PYR-41 and Thalidomide Impair Dendritic Cell Cross-Presentation by Inhibiting Myddosome Formation and Attenuating the Endosomal Recruitments of p97 and Sec61 via NF-κB Inactivation - Xiang You; Dan Dan Xu; Di Zhang; Jie Chen; Feng Guang Gao (Journal of Immunology Research)
PYR-41 and thalidomide have therapeutic effects on inflammation-associated diseases with side effects such as tumorigenesis. Cross-presentation allows dendritic cells (DC) to present endogenous antigen and induce protective immunity against microbe infection and tumors. But, up to now, the effects of PYR-41 and thalidomide on cross-presentation are still uncertain. In this study, we investigated the effect and mechanism of PYR-41 and thalidomide on DC cross-presentation by observing Myddosome formation, endosomal recruitment of p97 and Sec61, NF-κB activation, and cross-priming ability. We demonstrated that the inhibition of endosomal recruitment of p97 and Sec61, together with attenuated NF-κB activation and Myddosome formation, contributes to PYR-41- and thalidomide-impaired cross-presentation and thereby reverses cross-activation of T cells. These observations suggest that NF-κB signaling and p97 and Sec61 molecules are candidates for dealing with the side effects of PYR-41 and thalidomide.